Sharia-Based Evaluation of Village Fund Allocation for Infrastructure Development - Tarisa Zahrotur Rimaya; Munawir Munawir (Academia Open, 2025)
General Background: Effective village fund management is vital for advancing rural development, especially through infrastructure enhancement that directly supports community welfare. Specific Background: Karangmulyo village exemplifies the central role of village governance in allocating and utilizing these funds to deliver essential infrastructure. Knowledge Gap: Despite significant fund allocations, comprehensive assessments of fund effectiveness and alignment with Islamic economic principles remain limited. Aim: This study aims to evaluate the effectiveness of village fund utilization for infrastructure development in Karangmulyo village and to analyze it from an Islamic economic perspective. Results: The findings reveal that 81% of the village fund was effectively utilized in infrastructure development, aligning with standards set by the Minister of Home Affairs Decree No. 690.900.327/1996. Communication among stakeholders and adherence to procedures were satisfactory, despite constraints such as limited human resources and budget.Novelty: This research uniquely integrates conventional performance metrics with Islamic economic principles—mutual assistance (ta’awun), benefit (maslahah), and justice (‘adl)—to assess infrastructure governance. Implications: The study contributes to policy discourse on optimizing village fund use, emphasizing both administrative accountability and Sharia compliance as foundations for sustainable rural development. Highlights: Measures fund effectiveness using government benchmarks. Highlights barriers like limited resources and budget. Integrates Islamic economic values in development assessment. Keywords: Village Fund Management, Infrastructure Development, Islamic Economics, Rural Welfare, Sharia Compliance